Involvement of GABAergic and nitrergic systems in the anxiolytic and hypnotic effects of Curcuma longa: its interaction with anxiolytic-hypnotic - (:unkn) unknown (Walter de Gruyter GmbH, 2020)
Abstract Objectives Concurrent use of herbs with drugs have become a major healthcare problem. Herb-drug interactions could lead to therapeutic failure or toxicity. Hence, this study seeks to evaluate the impact of combining Curcuma longarhizome (CL) with selected anxiolytic and hypnotic drugs. Methods CL (100, 200 or 400 mg/kg, po) was administered to mice 1 h before subjecting the animals to elevated plus maze (EPM), hole board test (HBT), open field test (OFT) and rotarod test for anxiety- like effect as well as hexobarbitone-induced sleeping time (HIST) for hypnotic activity. The involvement of GABAergic and nitrergic systems in CL-induced anxiolytic and hypnotic actions were also evaluated. The effect of concurrent use of CL with midazolam, imipramine, nifedipine, Propranolol and carbamazepine were evaluated in anxiety-hypnosis models. Results The peak anxiolytic-like effect of CL was obtained at 400 mg/kg in the EPM and hole-board test without affecting muscle coordination in the rotarod test while the peak hypnosis-potentiation was observed at 100 mg/kg. CL-induced anxiolytic- Hypnotic-like effects were reversed by the pretreatment of mice with flumazenil or NG-nitro-l-arginine. Conclusions Curcuma longapossesses anxious and hypnotic effects through its interaction with GABAergic and nitrergic systems. Conversely, co-administration ofC. longawith midazolam potentiate barbiturate-induced hypnosis.
Keywords: Pharmacology (medical); General Pharmacology; Toxicology and Pharmaceutics link; University of Lagos; ACEDHARS; ACE: Drug Research, Herbal Medicine Development and Regulatory Science